Changing health behaviors under lockdown: the impact of the COVID-19 pandemic on adult physical activity and well-being - Grajek, Mateusz; Kujawińska, Maria; Duszyńska, Paulina; Grot, Martina; Kobza, Joanna (Journal of Education, Health and Sport, 2022)
Introduction. Obesity is recognized as one of the increasingly common diseases of civilization. It poses a great threat to the health and life of every person. Overweight and obesity have also been called a worldwide epidemic. Obesity is most often caused by prolonged positive energy balance: bad eating habits, low physical activity and other problems such as emotional. The current pandemic situation also promotes the incidence of overweight and obesity. Aim of the study. The main aim of the study was to investigate the impact of lockdown on the occurrence of overweight and obesity in adult population, while the specific aim was to investigate the impact of COVID-19 pandemic on the level of physical activity among adults. Material and Methods. A total of 244 adults participated in the study on the impact of lockdown on overweight and obesity. The criterion for inclusion in the study was a correctly completed questionnaire. The questionnaire was properly completed by 237 respondents, who were then qualified for further analysis. The study was conducted during the fall and winter seasons using a proprietary survey questionnaire. Data analysis was carried out using Microsoft Excel 2010, and the results and conclusions of the scientific study were obtained from it. Results and Conclusions. The results of the study indicate that the respondents do not have enough knowledge about proper nutrition. In addition, it was found that their physical activity is decreasing and they are working more and more often remotely, which limits their movement during the day.